FORMULATION AND IN-VITRO EVALUATION OF PARACETAMOL ORALLY DISINTEGRATING TABLETS USING DIFFERENT DISSOLUTION MEDIUMS (Journal of Medical & Health Sciences Review, 2025)
The primary objective of this study was to formulate and evaluate Paracetamol Orally Disintegrating Tablets (ODTs) using different superdisintegrants and to assess their performance in varying dissolution mediums. The aim was to develop a robust ODT formulation with rapid disintegration, acceptable mechanical strength, and enhanced dissolution profile for pediatric and geriatric use. Five formulations (F1-F5) of Paracetamol ODTs (120 mg) were prepared by direct compression. The formulations varied in the type and concentration of superdisintegrants: Sodium Starch Glycolate (SSG) and Crospovidone (CP). Pre- compression parameters of the powder blends were evaluated. The tablets were assessed for weight variation, hardness, friability, drug content, wetting time, in- vitro disintegration time, and in-vitro drug release in two different mediums: simulated salivary fluid (pH 6.8) and phosphate buffer (pH 5.8). All formulations exhibited good pre-compression properties with angle of repose between28.1°±0.6° and 32.5°±0.9°, indicating acceptable flow. Post-compression evaluation revealed that all tablets complied with pharmacopeial standards for weight variation (349.5±1.8 mg to 351.2±1.5 mg), hardness (3.2±0.3 to 4.1±0.2kg/cm²), friability (